2017
DOI: 10.1364/ol.42.002251
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high-power blue laser (445  nm) for material processing

Abstract: A blue diode laser has a higher absorption rate than a traditional laser, while the maximum power is limited. We report the structure and laser beam profile of a 250 W high-power blue laser (445 nm) for material processing. The absorption rate of the blue laser system for the steel was 2.75 times that of a single-mode fiber laser system (1070 nm). The characteristics of the steel after laser irradiation were determined, validating the potential of this high-power blue laser for material processing, such as hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…In the research of Prasad et al [69], in order to maintain the necessary heat input, compared with additively manufactured aluminum, steel and titanium, they use the largest power (1 kw) and the smallest speed (0.1 m/min). Other researchers are developing SLM technologies for blue and red lasers, but not much research has been done on pure copper [70,71].…”
Section: Selective Laser Meltingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the research of Prasad et al [69], in order to maintain the necessary heat input, compared with additively manufactured aluminum, steel and titanium, they use the largest power (1 kw) and the smallest speed (0.1 m/min). Other researchers are developing SLM technologies for blue and red lasers, but not much research has been done on pure copper [70,71].…”
Section: Selective Laser Meltingmentioning
confidence: 99%
“…In the study by Trevisan et al [5], a laser power of 200 w was also used and the substrate was preheated at 100 • C. The finally formed parts with a relative density of 83% were obtained. In the research of Wang et al [70], a SLM device based on blue laser (445 nm) was developed for the first time. It was found that the absorptivity of the steel powder to the blue laser was 2.5 times than the laser of wavelength range is 1000-1100 nm.…”
Section: Forming Properties Of Parts Manufactured By Slmmentioning
confidence: 99%
“…The rate of absorption of this laser system supplied on steel was 2.75 times that of the system of single-mode fiber laser operated at 1070nm. The steel characteristics after laser irradiation are commonly estimated to validate the potential of the used high-power blue laser to process materials such as cladding and heat treatment [6]. Xuan et al, in 2018, showed the generation of the deep ultraviolet lasers using solid-state/fiber lasers to process the nonlinear fundamental frequency conversion.…”
Section: -Introductionmentioning
confidence: 99%
“…As described in Smith's paper the quantum wells were distributed asymmetrically in a 4-3 configuration in the first two anti-nodes of the optical standing wave, resulting in laser emission at 672 nm with output power of 12.2 mW, limited by the available pump power of 500 mW [22]. Since this initial work the development and commercialization of multi-mode InGaN diode lasers has rapidly progressed, driven by numerous applications including material processing [26], communications [27] and lighting [28], such that low cost devices composed of multiple emitters mounted in TO-5 and TO-9 cans are now available with output powers of several W [29].…”
Section: Introductionmentioning
confidence: 99%